Steel Structures Design Based on Eurocode 3 - Hejazi, Farzad (Springer Singapore, 2018)
This book is tailored to the needs of structural engineers who are seeking to become familiar with the design of steel structures based on Eurocode 3. It explains each step of the design process using comprehensive flow charts, tables and equations as well as numerous examples. The useful appendices, including general sections and properties as well as general formulas for shear force, maximum bending moment and deflection for several selected loading conditions, offer designers a valuable source of reference. The book also introduces a specially developed design-aid program, which provides immediate results without the need for modeling, and as such considerably reduces the time needed for the design stage. .